Physicochemical and Microbial Properties of Fermented Milk from Swamp Buffalo: Comparison of The Original Methods of Dadiah Manufacturing and The Extended Method - Adila, Atika; Putra, Aronal Arief; Sandra, Afriani (Faculty of Animal Science, Universitas Brawijaya, 2025)
The fermentation methods used for buffalo milk sometimes vary among the regions where the Minangkabau people live. The physicochemical and microbial loads of fermented milk produced from swamp buffalo milk in this study were evaluated. The spontaneous method (in a bamboo tube), combination of spontaneous (in a bamboo tube) and backslopping (with the addition of a previous dadiah to the milk) methods, as well as its extension in the form of the backslopping method (with the addition of a dadiah to the milk in glass bottle), were applied in fermented milk manufacturing. The moisture content, pH, titratable acidity (TTA), and lactic acid bacteria load of the samples were analysed. The fermentation method had significant effects on the pH, TTA, and lactic acid bacteria load (P<0.05); in contrast, a comparable effect on moisture content was detected (P>0.05). The pH value of the samples prepared via the backslopping method and the combination of spontaneous and backslopping methods was lower than that of the spontaneous method (P<0.05), while a higher TTA was observed (P<0.05). Compared with the other methods, the combination method resulted in a higher lactic acid bacteria load, followed by the back slopping and spontaneous methods (P<0.05). The combination method might be considered the best method. In cases where bamboo is unavailable, the backslopping method can be used as an alternative method for buffalo milk fermentation to continue obtaining the live microflora benefits of the previous dadiah. In summary, confirmation from the original methods and the extended method provided more choices for the community to produce fermented milk from swamp buffalo milk.